Demographic Predictors of Work Ethics in a South African Sample - Jonck, Petronella; Van der Walt, Freda; Sobayeni, Caroline N. (African and Asian Studies, 2019)
Ethical behavior in South Africa, and consequently in the workplace, is currently a highly topical issue. Hence it was decided to investigate whether demographic differences exist regarding work ethics, in order to guide organizational decision-making and to understand work behavior in a South African sample. The sample consisted of 301 respondents, and data was collected using the Multidimensional Work Ethics Profile (MWEP), which was developed to measure seven facets of work ethics. Inferential statistical analysis was performed to analyze the dataset. The results indicate that male respondents scored higher on delay of gratification in comparison to their female counterparts. Test results for tenure found that increased years of service influenced respondents’ scores positively in hard work and delay of gratification.
Published Article
Keywords: Work Ethics; South Africa; Gender; Race; Highest Academic Qualification